Chemical Factors Underlying the More Rapid β-O-4 Bond Cleavage of Syringyl than Guaiacyl Lignin under Alkaline Delignification Conditions. (2nd November 2017) - Shimizu, Satoko; Akiyama, Takuya; Yokoyama, Tomoya; Matsumoto, Yuji
Abstract : This study aimed to clarify why the β- O -4 bond cleavage of syringyl lignin is more rapid than that of guaiacyl lignin under alkaline pulping conditions. We examined whether or not three chemical factors, acidity of the α-hydroxy group, nucleophilicity of the generated α-alkoxide, and leaving ability of the leaving phenoxide, are different between syringyl and guaiacyl lignins and control the rate of the alkaline-induced β- O -4 bond cleavage, employing dimeric non-phenolic β- O -4-type lignin model compounds (LMCs) and novel methods for estimating these three factors. The results indicated that the α-hydroxy groups of syringyl-type LMCs are relatively more acidic than those of guaiacyl-type and that syringyl nucleus is a better leaving group than guaiacyl nucleus in the β- O -4 bond cleavage. These factors result in the β- O -4 bond of syringyl lignin being more prone to the alkaline-induced cleavage than that of guaiacyl lignin.